The Clinical Analysis of Manic Episode Bipolar Patients with Psychotic Symptoms - Ivi Ayu Andriyana; Qurrota A'yuni Fitriana (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2024)
Bipolar is a mood disorder characterized by two extremes of emotion, manic and depressive. The two poles of emotion are opposite and can switch suddenly with no known time of recurrence. Extreme manic episodes can sometimes lead to symptoms of psychosis such as delusions and hallucinations. The research method used in this study is a qualitative method with a case study technique. Data collection was obtained through three stages, namely, observation, interviews and documentation. The purpose of this study is to describe in detail the experience of a bipolar disorder patient with psychotic symptoms who was treated at X Hospital. Through in-depth analysis of the course of the disease and the factors that influence the informant's condition. Based on the results of the study, the informant had been hospitalised twice with different diagnoses. The diagnosis of bipolar was obtained during the second hospitalisation. The informant had positive symptoms of hallucinations and delusions during the manic phase.